"For me it's just normal" - strategies of children and young people from rainbow families against de-normalisation - Sobočan, Ana Marija (Družboslovne razprave, 2013)
The paper presents some findings from an international study called "School isout - Experiences of children from rainbow families in school" which explored how children and young people from rainbow families anticipate, experience and deal with schools as heteronormative spaces. In the research, the term de-normalisation was developed to describe the processes by which children with LGBT-identified parents are perceived and constructed as not normal, as classified beyond the 'hetero-normative normality', which is expressed through 'othering' by others, for example in interaction. To avoid, prevent or reduce the impacts of de-normalisation processes, the interviewed children and youth have developed different strategies which we present in two frames: one involving disclosure and concealment and the other involving verbalisations and justifications. Based on these insights and findings, the article also outlines ideas on the resilience factors against de-normalisation and emphasises the importance of children and youth not standing alone against it.
Keywords: družina; family; istospolna družina; child; otroci; otroci iz istospolnih družin; denormalizacija; heteronormativnost; school; šola; homofobija; Slovenia; Slovenija; Nemčija; Germany